Jenis-Jenis Gastropoda di Pesisir Muara Kintap - Fatwatun Khasanah; Meyninda Destiara; Nurul Himmah (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
The typesof gastropods on thecoast of Muara Kintap will be carried out from August to December 2021. Gastropods are the largest group in the mollusca phylu, these animals are widely distributed in coastal marine areas, one of wich in on the coast of Muara Kintap. The coastal area is a natural habitat for gastropods. Line transect method was used to collect gastropod samples, namely; plot and take the gastropods inside. Gastropods faound 14 species, namely: Conus raulsilvai, Hexaplex trunculus, Hyalina pallida, Telescopium telescopium, Turitella communis, Turitella terebra L., Nucella lapillus, Naria eburnea, Nassarius phrrhus, Nassarius limmatus, Oliva trigidella oriolla, Cerithidea cingulata, Gibbula leucophea, Polinice didyma.